PENGARUH PENGGUNAAN MEDIA POWER POINT TERHADAP AKTIVITAS DAN HASIL BELAJAR SENI RUPA SISWA DI SMP N 4 PADANG - SEPTIA REZI, Drs. Eswendi, M.Pd., Dra. Ernis, M.Pd. (Universitas Negeri Padang, 2017)
This study aims to: (1) To determine the influence of media use powerpoint on the activity studied art student SMP N 4 Padang. (2) To determine the influence of media use powerpoint on learning outcomes art students of SMP N 4 Padang. This type of research is a quasi experimental quantitative research (quasi experimental) with pretest - posttest control group design. Classes are chosen as samples are a class VII-3 as the experimental class and class VII-4 as the control class. Data collected through achievement test instruments and test questionnaire learning activities. Data analysis is done processing stage descriptive and inductive analysis processing stage. The results showed that there are significant media use power point to the activity and the results studied art student at SMPN 4 Padang. Based on the results of hypothesis testing is done that the value of a hypothesis test on learning outcomes t = 15.546 and t table = 2.045 at the level of alpha = 0.05, it indicates that thitung> t table, it can be concluded Ha accepted. While testing the hypothesis on learning activities and rtabel rhitung = 4.762 = 0.334 at the level of alpha = 0.05, it indicates that rhitung> rtabel, it can be concluded Ha accepted, meaning that the average (mean) value of the experimental class and control class is not identical or different. It can be concluded that the use of media power point positive effect on activity and learning outcomes art students of SMPN 4 Padang.Keywords: Influence, Power Point Media, Activities, Learning Outcomes